How Schrödinger’s Cat Became a Zombie - Asprem, Egil (Method & theory in the study of religion, 2016)
Research on cultural transfers between science and religion has not paid enough attention to popular science. This article develops models that grasp the complexities of the epidemiology of science-based representations in non-scientific contexts by combining tools from the cognitive science of religion, the history, sociology, and philosophy of science, and the study of new religious movements. The popularization of science is conceptualized as a process of cognitive optimization, which starts with the communication efforts of scientists in science-internal forums and accelerates in popular science. The popularization process narrows the range of scientific representations that reach the public domain in structured ways: it attracts minimally counterintuitive representations, minimizes the massively counterintuitive, and re-represents (or translates) hard-to-process concepts in inferentially rich metaphors. This filtered sample trigger new processes of meaning-making as they are picked up and re-embedded in new cultural contexts.